Antipsychotic use in elderly patients and the risk of pneumonia. (January 2015) - Gambassi, Giovanni; Sultana, Janet; Trifirò, Gianluca
<x xml:space="preserve">Abstract</x> Antipsychotics are frequently and increasingly prescribed off-label for the treatment of behavioral and psychological symptoms associated with dementia, despite their modest efficacy. Instead, the safety profile of antipsychotics has been questioned repeatedly in recent years with various concerns, including death. Meta-analyses of randomized controlled trials found that one of the major causes of death associated with atypical antipsychotics use was pneumonia. Only few observational studies, however, have investigated the risk of pneumonia in elderly patients, especially among those receiving conventional antipsychotics. The aim of this editorial is to synthesize the current evidence from observational studies regarding the risk of pneumonia in elderly patients receiving either conventional or atypical antipsychotics. The studies conducted so far document that the risk of pneumonia is two- to threefold increased in a dose-dependent fashion with both classes compared to nonuse, with a possibly higher risk attributable to atypical antipsychotics. The risk seems to peak at the beginning of treatment (e.g., 7 – 30 days), and dissipates over time for both conventional and atypical antipsychotics. The risk–benefit ratio suggests that there will be 1 excess hospitalization for pneumonia for every 2 – 5 patients receiving any clinical improvement in symptoms. Considering the modest improvement in terms of efficacy, the risks associated with antipsychotics in elderly patients may outweigh their benefit.